Outcome of primary mediastinal large B-cell lymphoma using R-CHOP: impact of a PET-adapted approach - Hayden, Anna R; Tonseth, Petter; Lee, Derrick G; Villa, Diego; Gerrie, Alina S; Scott, David W; Freeman, Ciara L; Slack, Graham W; Farinha, Pedro; Skinnider, Brian; Yenson, Paul R; Benard, Francois; et al. (Blood, 2020)
Cure rates for primary mediastinal large B-cell lymphoma (PMBCL) have improved with the integration of rituximab. However, the type of primary therapy and role of radiotherapy (RT) remains ill-defined. Herein, we evaluated the outcome of PMBCL primarily treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) and the impact of an end-of-treatment (EOT) 18F-fluorodeoxyglucose positron emission tomography (PET) scan to guide consolidative RT. Patients ≥18 years of age with PMBCL treated with curative intent rituximab-chemotherapy were identified. Prior to 2005, patients were recommended to receive R-CHOP + RT (RT era). Beginning in 2005, EOT PET was used to guide RT and only those with a PET-positive scan received RT (PET era). In total, 159 patients were identified, 94% were treated with R-CHOP and 44% received RT (78% in RT era, 28% in PET era). The 5-year time to progression (TTP) and overall survival (OS) for the entire cohort were 80% and 89%, respectively, similar across treatment eras. Overall, 10% had refractory disease. In total, 113 patients had an EOT PET scan: 63% negative and 37% positive with a 5-year TTP of 90% vs 71% and 5-year OS of 97% vs 88%, respectively. For those with Deauville (D)-scored PET scans (n = 103), the 5-year TTP for PET-negative cases by Deauville criteria (D1-D3, DX) was 91%, with inferior outcomes for D5 vs D4 (5-year TTP 33% vs 87%, P = .0002). Outcomes for PMBCL treated with RCHOP are favorable and use of a PET-adapted approach reduces RT in the majority of patients. A small proportion have refractory disease and may benefit from an alternate treatment.